Challenges and opportunities for Tourism graduates in Peru under the Law 32392, the New General Tourism Law - Deza De la Vega, Fredy (2025)
This article analyzes the challenges and opportunities facing Licensed Tourism Professionals in Peru in light of the New General Tourism Law (Law 32392). The objective was to identify, from a critical and forward-looking perspective, howthis statute –already promulgated and in force– sets technical, institutional, and training requirements that these professionals must assume with responsibility, capability, and complete knowledge. Using a qualitative approach and a documentary research design, the legal provisions were examined with Law 32392 as the primary source and contrasted with recent academic and technical literature (mainly 2020-2025) and sectoral instruments such as PENTUR/PERTUR and PDTL plans, across four structural dimensions: governance and institutional framework, strategic planning, training and professionalization, and quality and innovation. The results show, on the one hand, that the Law does not expressly mention Licensed Tourism Professionals but does enable their technical participation in system governance, planning, quality/innovation mechanisms, and continuing training; and, on the other hand, that inter institutional articulation gaps and result-traceability issues persist and must be closed. It is concluded that the challenge is no longer to demand mere presence, but to consolidate visibility and institutionalize the technical role of Licensed Tourism Professionals, building it legitimately through professional practice. Proposed strategies include repositioning the professional association, reorienting university curricula, and creating a national observatory for the technical participation of graduates in Tourism.